2019
DOI: 10.3390/cancers12010081
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Label-Free Isolation of Tumour Cells from the Urine of Patients with Localised Prostate Cancer Using Inertial Microfluidics

Abstract: During the last decade, isolation of circulating tumour cells via blood liquid biopsy of prostate cancer (PCa) has attracted significant attention as an alternative, or substitute, to conventional diagnostic tests. However, it was previously determined that localised forms of PCa shed a small number of cancer cells into the bloodstream, and a large volume of blood is required just for a single test, which is impractical. To address this issue, urine has been used as an alternative to blood for liquid biopsy as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 24 publications
0
47
0
Order By: Relevance
“…Mediates cell adhesion to extracellular matrix 52 , 86 Glypicans Glypican-1 Upregulated in lymphoma, breast, pancreatic, and cervical cancer. Modulates mitogenic response 19 , 46 , 54 , 72 , 97 , 110 , 111 , 117 , 126 , 127 , 131 , 166 , 177 , 178 , 218 Glypican-3 Upregulated in hepatocellular, gastric, ovarian and lung squamous cell carcinoma; downregulated in breast, lung, ovary, and mesothelium cancers 67 , 86 , 153 …”
Section: Part B: the Role Of The Glycocalyx In Vascular Related Diseamentioning
confidence: 99%
See 1 more Smart Citation
“…Mediates cell adhesion to extracellular matrix 52 , 86 Glypicans Glypican-1 Upregulated in lymphoma, breast, pancreatic, and cervical cancer. Modulates mitogenic response 19 , 46 , 54 , 72 , 97 , 110 , 111 , 117 , 126 , 127 , 131 , 166 , 177 , 178 , 218 Glypican-3 Upregulated in hepatocellular, gastric, ovarian and lung squamous cell carcinoma; downregulated in breast, lung, ovary, and mesothelium cancers 67 , 86 , 153 …”
Section: Part B: the Role Of The Glycocalyx In Vascular Related Diseamentioning
confidence: 99%
“… 178 The use of GPC1 antibodies as a diagnostic tool to detect circulating tumor cells and exosomes, as well as labeling of cancer cells in situ , is an active area of investigation. 19 , 110 , 131 , 166 , 177 , 218 …”
Section: Part B: the Role Of The Glycocalyx In Vascular Related Diseamentioning
confidence: 99%
“…Studies have found that the cfDNA released by cells into the systemic circulation can also be filtered by the kidneys and transmitted in urine 7 , 8 . Therefore, scientists and clinicians are keen to utilize urine biopsies for the potential detection of diseases, including colorectal cancer (CC) 3 , bladder cancer (BC) 9 , chronic kidney disease 10 , prostate cancer (PC) 11 , cystic fibrosis 12 , and chronic obstructive pulmonary disease 13 .…”
Section: Components Of Urine Biopsymentioning
confidence: 99%
“…Several types of cells are present in urine, namely epithelial cells, renal-derived cells, leukocytes, erythrocytes and urothelial cells, as well as genetic material, proteins, peptides and inorganic elements. Therefore, scientific and medical personnel prefer to use urinary biopsies for the potential diagnosis of diseases, such as colorectal cancer (CC) [ 4 ], bladder cancer [ 3 ], chronic renal disease [ 6 ], prostate cancer [ 7 ], cystic fibrosis [ 8 ] and chronic obstructive pulmonary disease [ 9 ]. Urine may be used in its entirety or divided into supernatant and pellet for biomarker analysis.…”
Section: Introductionmentioning
confidence: 99%